Planning and implementation of project-based evaluation of general course learning outcomes - Widiyanto, Delfiyan; Wahyono, Hari; Istiqomah, Annisa; Ilham, Andri; Parnisiska, Arnianti (AIP conference proceedings, 2024)
Assessment of learning outcomes in general courses that have been carried out in learning has been carried out in the implementation of learning. One of the views is contained in the semester learning plan (RPS). General course learning outcomes vary, so researchers want to know the preparation and assessment of general course learning outcomes. The aim of this research is to find out the learning plan for general subjects (MKU) at Tidar University based on e-learning. This type of research is descriptive research using a qualitative approach. The subjects in this research were lecturers at MKU Tidar University. The object of this research is an e-learning based evaluation plan for MKU Tidar University learning outcomes. This research was conducted at Tidar University from March to September 2023. Data collection techniques in this research used interviews, observation and documentation. The research results show that lecturers have implemented learning outcomes by providing questions or confirmation, creating instruments, providing feedback and providing feedback to students with high performance. There are still lecturers who evaluate learning outcomes, do not prepare assessment rubrics, give assignments, and provide feedback with low performance.